Des corps « monstres ». Historique du stigmate féministe - Caroline Fayolle (Glad!)
This article analyses the stigmatization of pioneers in the struggle for women’s rights. By focusing on the monstrous figure of the « woman-man », it examines the pathologisation of feminism and the strategies of resistance developed by activists. Historicizing this anti-feminist rhetoric also highlights political challenges of contemporary feminism.